New method for the molecular recognition of thyroid hormones - MITROFAN, Grigorina; STEFAN-VAN STADEN, Raluca-Ioana; COMNEA-STANCU, Ionela-Raluca; VAN STADEN, Jacobus Frederick; ABOUL-ENEIN, Hassan Y.; KAPNISSI-CHRISTODOULOU, Constantina (Studia Universitatis Babeș-Bolyai Biologia, 2015)
The development of new methods that can detect a broad range of biomarkers became essential in modern medicine. The most frequent endocrine disorders include thyroid pathology. Stochastic sensors represent a unique class of single-molecule detectors and a promising candidate in biomedical analysis due to their ability to determine in one run more than one analyte. In clinical practice the main analytes used for the diagnosis and evolution of thyroid disease are free L-T3, L-T4 and TSH. A fast screening method based on stochastic sensors was proposed for the enantiorecognition of free L-T3, L-T4, D-T4 and TSH. Stochastic microsensors based on a mixture between two inulins (IN, TEX) and two ionic liquids (IN-L-Ala-C4-L-lac, IN-L-Phe-L-lac) immobilized on diamond paste (DP) were used for the assessment of thyroid hormones in whole blood samples. IN-L-Phe-C4-L-lac based microsensors showed the highest sensitivity for the assay of D-T4, L-T4 and TSH, while the highest sensitivity for L-T3 was obtained by using the stochastic microsensors based on IN-L-Ala-L-lac. The quantification limits obtained for thyroid hormones were: 10-12 mol/L for L-T4, 4x10-13 mol/L for L-T3, 6x10-12 for D-T4 mol/L and 5x10-15 g/mL for TSH. The microsensors determined the thyroid hormones in whole blood samples with high reliability: recoveries higher than 95.00%, and RSD (%) lower than 1.00%. The microsensors had great features in biomedical analysis for pattern recognition of thyroid hormones. This will help early detection of related diseases.